A hierarchical approach to supply chain simulation modelling using the Supply Chain Operations Reference model. (6th March 2007) - Pundoor, Guruprasad; Herrmann, Jeffrey W.
Simulation is a very useful tool for predicting supply chain performance. There is a need for standard simulation elements to represent the activities in a supply chain. This paper describes a novel supply chain simulation framework that follows the Supply Chain Operations Reference (SCOR) model. We use this framework to build simulation models that integrate discrete event simulation and spreadsheets. The simulation models are hierarchical and use submodels that capture activities specific to supply chains. We also describe a study that used this framework to analyse the impact of rescheduling frequency on the supply chain performance.